2018
DOI: 10.3390/f9060288
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nitrogen Utilization Capability during the Proliferation and Maturation Phases of Norway Spruce (Picea abies (L.) H.Karst.) Somatic Embryogenesis

Abstract: Somatic embryogenesis (SE) is a laboratory-based method that allows for cost-effective production of large numbers of clonal copies of plants, of particular interest for conifers where other clonal propagation methods are mostly unavailable. In this study, the effect of L-glutamine as an organic nitrogen source was evaluated for three contrasted media (containing NH 4 + NO 3 without glutamine, or glutamine + NO 3 , or glutamine without inorganic nitrogen) during proliferation and maturation of Norway spruce so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…Similar to our experiment on C. japonica , the best results for embryo maturation in Chamaecyparis pisifera [ 29 ], Larix decidua [ 30 ], Pinus nigra [ 31 ], and Picea abies [ 32 ] were obtained in media supplemented with low IN, rather than the high concentration in the other media tested. In contrast, a survey of SE in crop plants noted that 70% of the explants were cultured on an MS medium or a modified version of it [ 33 ].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Similar to our experiment on C. japonica , the best results for embryo maturation in Chamaecyparis pisifera [ 29 ], Larix decidua [ 30 ], Pinus nigra [ 31 ], and Picea abies [ 32 ] were obtained in media supplemented with low IN, rather than the high concentration in the other media tested. In contrast, a survey of SE in crop plants noted that 70% of the explants were cultured on an MS medium or a modified version of it [ 33 ].…”
Section: Resultssupporting
confidence: 82%
“…Organic nitrogen is essential for the production of healthy embryos during SE, and glutamine is one of the most common sources of organic nitrogen reported in conifers [ 32 , 61 ]. The addition of glutamine, asparagine, arginine, and other AAs to the maturation medium has been commonly used to enhance the maturation efficiency of somatic embryos [ 2 , 5 , 29 , 35 , 45 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Removing inorganic nitrogen from the germination media, which led to a decrease in the total amount of nitrogen in the germination media, also had a large impact on root growth during five weeks of in vitro germination (Paper I). The results herein support previous findings, in which the growth of emblings and seedlings is enhanced when less nitrogen is used (see, e.g., Brouwer 1962;Ingestad and Kähr 1985;Kaakinen et al 2004;Gruffman et al 2012;Dahrendorf et al 2018;Llébres et al 2018a, b). Due to the improved root growth, a germination medium without inorganic nitrogen was introduced in the standard protocol.…”
Section: Yield Survival and Height Growth After Improvements (Paperssupporting
confidence: 92%
“…The source of organic nitrogen is an important component of the culture media for the success of the SE process, and in this sense, amino acids are commonly used to improve the maturation of ses, modifying its type and concentration (Gerdakaneh et al, 2011;Satish et al, 2016;Dahrendorf et al, 2018). As Maruyama et al (2021) reported, the presence of organic nitrogen improved the production of ses.…”
Section: Introductionmentioning
confidence: 99%
“…As Maruyama et al (2021) reported, the presence of organic nitrogen improved the production of ses. Casein and glutamine are usually used in the SE of conifers (Afele and Saxena, 1995;Pullman and Bucalo, 2014;Dahrendorf et al, 2018), but, in some species, such as Pinus patula Schiede ex Schltdl. and Cham.…”
Section: Introductionmentioning
confidence: 99%